2004
DOI: 10.1080/01436590410001678898
|View full text |Cite
|
Sign up to set email alerts
|

Hyper‐self‐reflexive development? Spivak on representing the Third World ‘Other’

Abstract: struggle'in a way that ignores the international division of labour (19BBa: 272-274). She goes on to show how colonial and 'native' representations are similarly problematic. Focusing on widow-sacrifice (sati) in colonial India, she examines the British move to abolish the practice, which wasjustified on the basis of the British'civilising mission'in India (a move which Spivak captures in the now famous phrase: 'White men saving brown women from brown men') (19BBa: 297). She contrasts this position with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
183
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(190 citation statements)
references
References 25 publications
2
183
0
5
Order By: Relevance
“…The Cameroonian state and NGOs as development actors are instead 'speaking for' (political representation) and 'speaking about' or 'representing' the subaltern Pygmies in the sense of producing a portrait of these indigenous peoples. The proclivity of dominant discourses and institutions are instead marginalizing, disempowering and erasing the Pygmies in the name of development (see Spivak, 1998, Kapoor, 2004. Hewlett (2000:385) notes that Cameroonian government officials were proud of helping the Baka, rather than leaving them to die out, despite official perceptions that they are at a low stage of evolution, have few redeeming traits and low social value.…”
Section: Resultsmentioning
confidence: 99%
“…The Cameroonian state and NGOs as development actors are instead 'speaking for' (political representation) and 'speaking about' or 'representing' the subaltern Pygmies in the sense of producing a portrait of these indigenous peoples. The proclivity of dominant discourses and institutions are instead marginalizing, disempowering and erasing the Pygmies in the name of development (see Spivak, 1998, Kapoor, 2004. Hewlett (2000:385) notes that Cameroonian government officials were proud of helping the Baka, rather than leaving them to die out, despite official perceptions that they are at a low stage of evolution, have few redeeming traits and low social value.…”
Section: Resultsmentioning
confidence: 99%
“…Da die Geographische Entwicklungsforschung und die Postcolonial Studies bereits aufgrund ihrer Forschungsgegenstände zahlreiche Berührungspunkte aufweisen, verwundert gerade der geringe Austausch zwischen diesen beiden Forschungsrichtungen (McEwan, 2009:1;Radcliffe, 2005;Simon, 2006). Arbeiten, die sich in ihrem Schnittfeld verorten lassen, beschäftigen sichüberwiegend mit selbstreflexiven Analysen und fragen nach den postkolonialen Machtverhältnissen und Epistemologien, die den " eigenen" Forschungsprojekten und Lehrveranstaltungen im oderüber " den Globalen Süden" unterliegen (Abbot, 2006;Kapoor, 2004;McEwan, 2009:295f;Raghuram und Madge, 2006). Auffällig ist, dass gegenüber den dekonstruktivistischen Herangehensweisen dieser Arbeiten kaum empirische Studien im Bereich der Geographischen Entwicklungsforschung vorliegen, die auf Ansätzen der postkolonialen Theorie basieren und darauf abzielen, "…”
Section: Geographische Entwicklungsforschung Postkoloniale Kritik Ununclassified
“…Some of these discussions of responsibility have centred around addressing inequality, in particularly the responsibilities of richer countries and people towards those who are less wealthy or distanciated, often evoked through the figure of the ‗distant stranger' (Patai, 1991;Corbridge, 1993Corbridge, , 1998Smith, 2002). Other studies have revealed the distinctive temporal dimensions of these relationships, both the importance of the past in shaping the present (Andreasson, 2005;Biccum, 2005;Cupples et al, 2007;Kapoor, 2004;Sharpe and Briggs, 2006) and also the need to think about responsibility to those who will come in the future, especially in relation to the environment (Armstrong, 2006;Baldwin, 2004;Hillman, 2004;Hobson, 2006;Richardson, 2004) 3 . In this wide ranging literature on geographies of responsibility, 11 we identify two key themes, which resonate with the care literature: responsibility as ethical place-making; and relationships and (re)arrangements between places.…”
Section: Geographies Of Responsibilitymentioning
confidence: 99%